Prevalence of the Brazilian TP53 Founder c.1010G>A (p.Arg337His) in Lung Adenocarcinoma: Is Genotyping Warranted in All Brazilian Patients? - Vieira, Igor Araujo; Andreis, Tiago Finger; Fernandes, Bruna Vieira; Achatz, Maria Isabel; Macedo, Gabriel S.; Schramek, Daniel; Ashton-Prolla, Patricia (Frontiers in Genetics, 2021)
In Southern and Southeastern Brazil, there is a germline pathogenic variant with incomplete penetrance located in the oligomerization domain of TP53, c.1010G>A (p.Arg337His). Due to a founder effect, the variant is present in 0.3% of the general population of the region. Recently, this variant was identified in 4.4% and 8.9% of two apparently unselected, single center case series of Brazilian lung adenocarcinoma (LUAD) patients from the Southeastern and Central regions of the country, respectively. In the present study, our aim was to examine TP53 c.1010G>A allele and genotype frequencies in LUAD samples obtained from patients diagnosed in Southern Brazil. A total of 586 LUAD samples (tumor DNA) recruited from multiple centers in the region were tested, and the mutant allele was identified using TaqMan® assays in 7 cases (7/586, 1.2%) which were submitted to next generation sequencing analyses for confirmation. Somatic EGFR mutations were more frequent in TP53 c.1010G>A carriers than in non-carriers (57.1% vs. 17.6%, respectively). Further studies are needed to confirm if TP53 c.1010G>A is a driver in LUAD carcinogenesis and to verify if there is a combined effect of EGFR and germline TP53 c.1010G>A. Although variant frequency was higher than observed in the general population, it is less than previously reported in LUAD patients from other Brazilian regions. Additional data, producing regional allele frequency information in larger series of patients and including cost-effectiveness analyses, are necessary to determine if TP53 c.1010G>A screening in all Brazilian LUAD patients is justified.